Protective effect of histone methyltransferase NSD3 on ISO‐induced cardiac hypertrophy. Issue 18 (12th July 2019) - Chen, Ke; Jian, Dongdong; Zhao, Linwei; Zang, Xiaobiao; Song, Weifeng; Ma, Jifang; Jia, Zhen; Wang, Xianqing; Gao, Chuanyu
Abstract : Nuclear receptor‐binding SET domain 3 (NSD3) is a lysine methyltransferase that plays important roles in multiple biological activities; however; its potential roles in the cardiovascular system remain unknown. In this study, we found that NSD3 expression is reduced by isoproterenol (ISO) stimuli both in vitro and in vivo . Overexpression of NSD3 attenuates ISO‐induced cardiomyocyte hypertrophy. Mechanistically, ISO treatment decreases H3K27me2/3 modifications on the atrial natriuretic factor (ANF) promoter by suppressing NSD3 and inhibits the association between NSD3 and bromodomain‐containing protein 4 (BRD4), thus suppressing the BRD4‐mediated H3K27ac modifications, which ultimately promote ANF transcription and cardiomyocyte hypertrophy. In conclusion, NSD3 decreases ANF expression and, thereby, attenuates ISO‐induced cardiomyocyte hypertrophy. Abstract :